Policy Performance in the Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics within Local Context: A Critical Evaluation of the National Narcotics Board in Palu City - Imam Hanafi; Agusta Sri Astuti (Lembaga Bale Literasi, 2025)
This Drug abuse and illicit trafficking represent critical challenges threatening national security and public welfare in Indonesia. The National Narcotics Board (BNN) implements comprehensive policies through the P4GN program (Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics), yet local implementation effectiveness remains underexplored. This study evaluates the performance of P4GN policy implementation by the Palu City National Narcotics Board within the local context, applying Dunn's policy evaluation framework. A qualitative approach was employed utilizing in-depth interviews with five informants (four BNN Palu officials and one drug user), direct observation, and documentation analysis. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldana (2014). The evaluation framework incorporated Dunn's five criteria: effectiveness, efficiency, adequacy, equity, and responsiveness. The P4GN policy demonstrates moderate effectiveness in prevention and rehabilitation, particularly within educational institutions and formal organizations. However, significant challenges persist, including limited human resources, insufficient budgetary allocations, and suboptimal inter-agency coordination. Community empowerment programs and services in peripheral areas exhibit uneven distribution. Efficiency and equity remain constrained due to inadequate rehabilitation facilities and predominantly administrative evaluation mechanisms rather than outcome-based assessments. While the P4GN policy in Palu City shows reasonable responsiveness to situational changes, substantial improvements are needed in efficiency, contextual appropriateness to local conditions, and results-based evaluation systems. Recommendations include strengthening cross-sectoral coordination, enhancing human resource capacity, and adopting community-based approaches incorporating local wisdom for sustainable policy effectiveness.